KOMPERASI PEMBAGIAN HARTA WARISAN PRESPEKTIF HUKUM PERDATA DAN HUKUM ISLAM - Fauzan Al-As’ari; Ali Khosim; M Athoillah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The distribution of inheritance is a crucial aspect of family law that often leads to conflict among heirs. This study aims to analyze and compare the concept of inheritance distribution from the perspectives of civil law and Islamic law. The research method used is library research, analyzing relevant sources of civil law and Islamic law. The results show that civil law regulates the distribution of inheritance based on the principles of individuality, bilaterality, and equality, where each heir receives an individual share without distinction of gender. Meanwhile, Islamic law regulates the distribution of inheritance based on the principles of justice and equality, where heirs receive shares in accordance with Islamic law. The conclusion of this study is that the distribution of inheritance from the perspectives of civil law and Islamic law differs in terms of the principles and principles used. However, both perspectives share the same goal: to create justice and order in the distribution of inheritance.